2011
DOI: 10.1590/s1517-83822011000100036
|View full text |Cite
|
Sign up to set email alerts
|

Hematology and productive performance of nile tilapia (Oreochromis niloticus) naturally infected with Flavobacterium columnare

Abstract: Columnaris disease is one of the main causes of mortality in tilapia rearing and is responsible for large economic losses worldwide. Hematology is a tool that makes it possible to study organisms' physiological responses to pathogens. It may assist in making diagnoses and prognoses on diseases in fish populations. The hematological variables of nile tilapia were studied in specimens with a clinical diagnosis of columnaris disease and in specimens that were disease-free. The total erythrocyte count, hemoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 31 publications
(15 reference statements)
2
27
1
1
Order By: Relevance
“…Sebastião et al [72] reported a neutrophilia response in Nile tilapia after Flavobacterium columinare challenge, similar to our study; they also simultaneously reported an increase in circulating lymphocyte counts, which contradict our findings. Moreover, Ali and Ansari [73] reported a synchronized neutrophilia and lymphopenia response in common carp after monogenean (flukes) challenge, which is in agreement with our findings.…”
Section: S Iniaecontrasting
confidence: 72%
“…Sebastião et al [72] reported a neutrophilia response in Nile tilapia after Flavobacterium columinare challenge, similar to our study; they also simultaneously reported an increase in circulating lymphocyte counts, which contradict our findings. Moreover, Ali and Ansari [73] reported a synchronized neutrophilia and lymphopenia response in common carp after monogenean (flukes) challenge, which is in agreement with our findings.…”
Section: S Iniaecontrasting
confidence: 72%
“…In this study, growth rates were improved by ASP supplementation, and haematocrit, haemoglobin levels, RBC counts and WBC counts were also upregulated. It has been assumed that dietary probiotics can upregulate blood biomarkers in fish as indicators of improved health status (Panigrahi, Kiron, Satoh, & Watanabe, ; Serbastiao, Nomura, Sakabe, & Pilarski, ). Probiotics have a competitive ability against pathogenic bacteria in the GIT, by the production of peroxide, bacteriocin, siderophore and lysozyme enzymes which may result in improved immunity and health status (Fuller, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, with the rapid development of the tilapia culture industry, various bacterial diseases frequently outbreak due to intensified culture and high stocking density conditions of intensive farming. Pathogens, such as streptococcosis (Anshary, Kurniawan, Sriwulan, Ramli, & Baxa, ; Verner‐Jeffreys et al., ), edwardsiellosis (Kwon, Nam, Kim, & Kim, ; Park & Jeong, ; Soto, Illanes, Revan, Griffin, & Riofrio, ; Soto et al., ), columnaris disease (Dong, Lafrentz, Pirarat, & Rodkhum, ; Sebastiao, Nomura, Sakabe, & Pilarski, ), francisellosis (Assis, Tavares, Pereira, Figueiredo, & Leal, ; Ortega et al., ; Sebastiao, Pilarski, Kearney, & Soto, ) and motile aeromonas septicaemia (Dong et al., ; Li & Cai, ; Soto‐Rodriguez, Cabanillas‐Ramos, Alcaraz, Gomez‐Gil, & Romalde, ), have resulted in substantial economic losses to the local aquaculture industries.…”
Section: Introductionmentioning
confidence: 99%